(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Left Main (LM) coronary artery disease and left ventricular dysfunction both are important predictors of in-hospital mortality. To avoid the harmful effects of cardio pulmonary bypass (CPB), many cardiac surgeons are using Off pump Coronary Artery Bypass (OPCAB) as an effective alternative to conventional CABG (CCAB) even in these sub-groups of patients. This study performed in the National Institute of Cardiovascular Diseases (NICVD) evaluated the early outcomes of OPCAB in terms of mortality and major post-operative morbidities and compared them with that of CCAB in patients with left main coronary artery diseases with left ventricular (LV) dysfunction. Total 120 patients with left main coronary artery disease with reduced left ventricular ejection fraction (<_40%) were allocated into two groups: a) 60 patients who underwent OPCAB and b) another 60 patients who underwent conventional CABG between January 2012 and December 2017. All risk factors and co-morbidities were homogenously distributed between the two groups. Majority of the patients had triple vessel disease. Nearly three-quarters (73.3%) of patients in OPCAB group and 80% in CCAB group received 3 grafts (p=0.470). The mean total operative time (p< 0.001), intubation times (p<0.001), blood losses (p < 0.001); requirements for blood and blood products (p < 0.0010), intensive care unit stays (p<0.001) and hospital stays (p< 0.001) were all significantly lower in the OPCAB group. OPCAB is a safe and effective operative revascularization procedure for patients with left main coronary artery disease with left ventricular dysfunction and is associated with reduced morbidity. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):04-08